Comparison on characteristic of Mesoparticle Graphene Sand Composite (MGSC) using different types of sugar to remove methylene blue - Zularisam, A. W.; Norul Wahida, Kamaruzaman; Ahmad, Alfian (IOP Publishing, 2017)
This paper presents the green method to synthesis two types of adsorbent called mesoparticle graphene sand composite (MGSC) by using table sugar (MGSCts) and arenga palm sugar (MGSCaps) as different carbon sources to remove methylene blue acted as a dye model. Immobilisations of these materials on sand were introduced by using pyrolysis method without binder usage. Sand was treated by removing deleterious materials before sieved. The solutions of sugar were prepared and heated to 95 °C. The sand and sugar solutions were mixed and constantly stirred before putting them in furnace with nitrogen environment to produce MGSCts and MGSCaps. The composites were activated by using concentrated sulphuric acid to open the pores and maximise the capacity of absorbency. The analyses on the characteristic of both MGSCts and MGSCaps were conducted through field emission scanning electron microscope (FESEM), elemental dispersive x-ray (EDX) and elemental mapping (EM). FESEM analyses exhibited that the coating process was done uniformly as there were layers of coating sheets formation on the sand particles surfaces. After conducting EDX and EM, there were major elements found in both MGSCts and MGSCaps which were carbon, oxygen and silica. EM exhibited the distribution of these elements were scattered on the MGSC's surfaces. Removal of methylene blue was successfully carried out by using both MGSCts and MGSCaps, with maximum removal up to 40% at the first hour of contact time.